Money and Unethical Behavior of Accounting Students - Dewi, Luh Gede Krisna; Dewi, Ayu Aryista (Universitas Negeri Malang, 2018)
Financial fraud involving the accounting profession lower public confidence in the accounting profession and the presentation of financial statements. The need for early detection of the factors causing a person to commit an unethical behavior is increasing. Accounting students as individuals who will enter the workforce and become accounting professionals are expected to get accounting ethics education correctly. This study aimed to analyze the relationship among the love of money, the machiavellian behavior, the unethical behavior, and gender as demographic variables. Respondents were active undergraduate students in Accounting Department. The sampling technique used purposive sampling with sample amounted to 234 respondents. Data collection was conducted through questionnaires containing 34 items of questions related to the behavior of love of money, Machiavellian, and unethical behavior. The results found that Machiavellian behavior can mediate the influence of love of money on the unethical behavior of Accounting students. Men tend to choose to take risks in action than women, so this research indicated that gender as demographic variables can also affect the relationship of love of money to unethical behavior.